Two-component transparent polyurea coating and preparation method thereof

By introducing tin antimony oxide, nano-silica and polydopamine-coated fillers, as well as fluorine-containing maleate and end-epoxy silicone oil into polyurea coatings, the problem of softening and decomposition of polyurea coatings at high temperatures has been solved, and the problem of softening and decomposition of polyurea coatings has been improved. Its thermal stability and aging resistance extend the service life and enhance high temperature and hydrophobicity.

CN118745317BActive Publication Date: 2024-12-13BEIJING EONZEAL WATERPROOF MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410930831.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2024-12-13
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

Polyurea coatings are prone to softening or decomposing under high temperature environments, causing the coating to discolor, decompose and fail, seriously affecting its service life.

Method used

The preparation method of two-component transparent polyurea coating is adopted. By mixing and dispersing tin antimony oxide and nano-silica, reacting with para-aniline sulfonic acid to form a composite filler, and the compatibility is improved by using polydopamine coated filler. Fluorine-containing maleate and end-epoxy silicone oil are introduced to enhance the thermal stability and hydrophobicity of the coating.

Benefits of technology

It effectively improves the thermal stability, aging resistance and toughness of polyurea coatings, extends its service life, and enhances high temperature resistance and hydrophobicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The present invention provides a two-component transparent polyurea coating and a preparation method thereof, belonging to the technical field of coatings; the preparation process thereof comprises the following steps: adding antimony tin oxide and nano-silicon dioxide to prepare a composite filler; adding dopamine to prepare a polydopamine coated filler; adding 4,4′-dicyclohexylmethane diisocyanate to prepare component A; preparing fluorinated maleate; adding fluorinated maleate to prepare component B; mixing component A and component B to prepare a polyurea coating. The present invention is to disperse antimony tin oxide and nano-silicon dioxide in deionized water, and then react with p-aniline sulfonic acid to perform surface functionalization, and then react with aniline and phytic acid under the initiation of ammonium persulfate to form a composite filler, and finally use polydopamine to coat the composite filler, and add the polydopamine coated filler to the polyurea coating, which can effectively improve the thermal stability and aging resistance of the polyurea coating, thereby extending the service life of the polyurea coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a two-component transparent polyurea coating and a preparation method thereof. Background Art

[0002] Polyurea is an elastomeric material formed by the reaction of isocyanate components and amino compounds. It is a new type of pollution-free, solvent-free, high-performance green coating containing repeated urea groups in its molecular structure. It has many advantages such as high solid content, fast curing speed, low viscosity and high mechanical properties. It is widely used in parts, steel structures, concrete and other industries.

[0003] Polyurea coatings form a highly cross-linked network structure through the reaction of diisocyanates and amine compounds. Although this high degree of cross-linking gives the coating excellent mechanical properties and chemical stability, it also makes the material more susceptible to softening or decomposition at high temperatures. The temperature resistance range of polyurea coatings is generally between -40°C and 120°C. Exceeding this temperature range, especially in a long-term high temperature environment, the chemical bonds of polyurea coatings are prone to breakage, causing the coating to discolor, decompose or even fail, seriously affecting the service life of the polyurea coating.

[0004] Based on this, we propose a two-component transparent polyurea coating with high temperature resistance and a preparation method thereof to extend its service life. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a two-component transparent polyurea coating and a preparation method thereof.

[0006] A method for preparing a two-component transparent polyurea coating comprises the following steps:

[0007] S1: Preparation of composite fillers by adding antimony tin oxide and nano-silicon dioxide

[0008] Antimony tin oxide and nano silicon dioxide are dispersed in deionized water, p-aniline sulfonic acid is added to react, and then mixed with aniline, phytic acid and ammonium persulfate to react to obtain a composite filler;

[0009] S2: Preparation of polydopamine-coated fillers by adding dopamine

[0010] The composite filler is dispersed in deionized water, and then tris(hydroxymethyl)aminomethane and dopamine are added to react to obtain a polydopamine-coated filler;

[0011] S3: Add 4,4′-dicyclohexylmethane diisocyanate to prepare component A

[0012] Heat and stir polytetramethylene glycol, then add 4,4′-dicyclohexylmethane diisocyanate to react, and then add the polydopamine coated filler to obtain component A;

[0013] S4: Preparation of fluorinated maleates

[0014] Maleic anhydride and ethylene glycol monododecafluoroheptyl ether are stirred and mixed, and aminosulfonic acid and toluene are added to react to obtain fluorine-containing maleate;

[0015] S5: Add fluorinated maleate to prepare component B

[0016] The amino-terminated polyether and the epoxy-terminated silicone oil are stirred and mixed to react, and then the fluorinated maleate is added to react to obtain component B;

[0017] S6: Mixing component A and component B to prepare polyurea coating

[0018] When in use, the above component A and component B are uniformly mixed in a mass ratio of 1:(1-3) to obtain a polyurea coating.

[0019] Furthermore, S1 specifically includes the following steps:

[0020] S1.1: Add antimony tin oxide and nano-silicon dioxide in a mass ratio of (2-3):1 into deionized water at a solid-liquid ratio of 1g:(45-55)mL, and disperse them by ultrasonic for 20-30min. Then add p-anilinesulfonic acid, stir and disperse, and heat at 70-80℃ for 8-10h to react to obtain a suspension.

[0021] S1.2: filtering the suspension through a water-based microporous mixed cellulose lipid membrane, washing with deionized water and ethanol for 2-3 times respectively, and freeze-drying to obtain a surface functionalized mixed material;

[0022] S1.3: Add the surface functionalized mixture to deionized water at a solid-liquid ratio of 1 g: (20-30) mL, disperse by ultrasonic for 10-20 min, then add aniline, stir at 2-10°C for 30-40 min, and mix evenly to obtain a dispersion;

[0023] S1.4: Keeping the temperature constant, add phytic acid to the above dispersion until the phytic acid concentration reaches 1 mol / L, then add ammonium persulfate, stir and react for 10-12 hours, filter, wash and freeze-dry to obtain a composite filler.

[0024] Furthermore, S2 specifically includes the following steps:

[0025] S2.1: ultrasonically disperse the composite filler obtained in step S1.4 in deionized water at a solid-liquid ratio of 1 g: (30-40) mL, then add tris(hydroxymethyl)aminomethane, maintain the pH at 8-9, and obtain a mixed solution;

[0026] S2.2: Add dopamine to the mixed solution, stir at room temperature for 13-15 hours to react and obtain a suspension;

[0027] S2.3: Place the above suspension in a high-speed centrifuge, centrifuge at a rate of 8000-10000 r / min for 30-40 min, collect the precipitate, and then wash and dry the precipitate to obtain a polydopamine-coated filler.

[0028] Furthermore, S3 specifically includes the following steps:

[0029] S3.1: Heat polytetrahydrofuran ether diol at 95-100°C with stirring for 20-30 min under nitrogen protection;

[0030] S3.2: When the temperature of polytetramethylene glycol is reduced to 30-40°C, 4,4′-dicyclohexylmethane diisocyanate is added, and then heated at 70-80°C while stirring for 2-4 hours to react, and filtered to obtain a precursor product, wherein the molar ratio of polytetramethylene glycol to 4,4′-dicyclohexylmethane diisocyanate is (1.5-2.5):1;

[0031] S3.3: Add the polydopamine-coated filler obtained in step S2.3 to the above-mentioned precursor product at a solid-liquid ratio of 1g:(55-75)mL, stir and mix evenly to obtain component A.

[0032] Furthermore, S4 specifically includes the following steps:

[0033] S4.1: maleic anhydride and ethylene glycol monododecafluoroheptyl ether are added into a reactor at a molar ratio of 1:(2-3), and stirred to mix well to obtain a mixed reaction liquid;

[0034] S4.2: Add sulfamic acid and toluene to the mixed reaction solution, stir and mix evenly, and then heat at 110-120° C. for 14-18 hours to react to obtain a crude product;

[0035] S4.3: The crude product is filtered to remove aminosulfonic acid, and then distilled under reduced pressure to remove impurities to obtain fluorinated maleate.

[0036] Furthermore, S5 specifically includes the following steps:

[0037] S5.1: Mix the amino-terminated polyether and the epoxy-terminated silicone oil in a molar ratio of (1.5-2.5): 1 and then heat at 80-90°C for 8-10h under the protection of nitrogen to react and obtain an intermediate;

[0038] S5.2: When the intermediate is cooled to 50-60°C, the fluorinated maleate prepared in step S4.3 is added, and then the temperature is raised to 75-85°C, and the mixture is reacted for 4-5 hours while stirring to obtain component B, wherein the molar ratio of the fluorinated maleate to the amino-terminated polyether is (1.8-2.2):1.

[0039] Furthermore, the mass ratio of the total amount of antimony tin oxide and nano-silicon dioxide to p-aniline sulfonic acid is 1:(15-18), the mass ratio of aniline to the surface functionalized material is (18-20):1, and the mass ratio of ammonium persulfate to the surface functionalized material is (20-24):1.

[0040] Furthermore, the mass ratio of tris(hydroxymethyl)aminomethane to the composite filler is (8-12):1, and the mass ratio of dopamine to the composite filler is (2-4):1.

[0041] Furthermore, the amount of aminosulfonic acid added is (0.6-0.8) g / 0.1 mol maleic anhydride, and the mass ratio of toluene to aminosulfonic acid is (6.5-8.5):1.

[0042] A two-component transparent polyurea coating is prepared by any one of the above-mentioned methods for preparing a two-component transparent polyurea coating.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. The present invention disperses antimony tin oxide and nano-silicon dioxide in deionized water, reacts with p-anilinesulfonic acid to perform surface functionalization, and then reacts with aniline and phytic acid under the initiation of ammonium persulfate to form a composite filler. Finally, the composite filler is coated with polydopamine to improve the compatibility between the composite filler and the polyurea coating. The polydopamine-coated filler is added to the polyurea coating, which can effectively improve the thermal stability and aging resistance of the polyurea coating, thereby extending the service life of the polyurea coating.

[0045] 2. The present invention first reacts maleic anhydride and ethylene glycol monododecafluoroheptyl ether under the catalysis of aminosulfonic acid to prepare fluorine-containing maleate, then reacts the fluorine-containing maleate with an intermediate to prepare component A, and after mixing component A with component B to prepare a polyurea coating, due to the introduction of fluorine-containing groups, fluorine atoms have a good protective effect on the molecular chain, thereby effectively improving the hydrophobicity and high temperature resistance of the polyurea coating.

[0046] 3. The present invention heats and reacts terminal amino polyether and terminal epoxy silicone oil to prepare an intermediate, and then mixes the intermediate with fluorinated maleate to react to prepare component A. After component A is mixed with component B to prepare a polyurea coating, the terminal epoxy silicone oil migrates to the molecular surface, thereby increasing the decomposition temperature, thereby effectively improving the high temperature resistance of the obtained polyurea coating. Moreover, since the terminal epoxy silicone oil chain segment is elastic and flexible, while the polyurea chain segment is rigid, the flexible and rigid chain segments are combined with each other, and can be better curled and deformed, thereby improving the toughness of the obtained polyurea coating. DETAILED DESCRIPTION

[0047] The following is a detailed description of a two-component transparent polyurea coating and a preparation method thereof provided by the present invention in conjunction with specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies.

[0048] In the following examples and comparative examples, the particle size of antimony tin oxide is 20-25 nm, and the average particle size is 22 nm; the particle size of nano silicon dioxide is 20-30 nm, and the average particle size is 24 nm.

[0049] Example 1

[0050] A method for preparing a two-component transparent polyurea coating comprises the following steps:

[0051] S1: Preparation of composite fillers by adding antimony tin oxide and nano-silicon dioxide

[0052] Antimony tin oxide and nano-silicon dioxide were added to deionized water at a mass ratio of 2:1 according to a solid-liquid ratio of 1g:45mL, ultrasonically dispersed for 20min, and then p-aniline sulfonic acid was added. After stirring and dispersing, the mixture was heated at 70°C for 8h to react to obtain a suspension, wherein the mass ratio of the total amount of antimony tin oxide and nano-silicon dioxide to p-aniline sulfonic acid was 1:15. The suspension was then filtered with an aqueous microporous mixed cellulose lipid membrane, washed twice with deionized water and ethanol respectively, and freeze-dried to obtain a surface functionalized mixed material. Subsequently, the mixture was added to a solid-liquid ratio of 1g : 20mL of the surface functionalized mixed material was added into deionized water, ultrasonically dispersed for 10 minutes, and then aniline was added, and stirred at a temperature of 2°C for 30 minutes, and uniformly mixed to obtain a dispersion, wherein the mass ratio of aniline to the surface functionalized material was 18:1. Finally, phytic acid was added to the dispersion while keeping the temperature constant until the phytic acid concentration reached 1 mol / L, and then ammonium persulfate was added, stirred for reaction for 10 hours, filtered, washed and freeze-dried to obtain a composite filler, wherein the mass ratio of ammonium persulfate to the surface functionalized material was 20:1.

[0053] S2: Preparation of polydopamine-coated fillers by adding dopamine

[0054] The composite filler prepared in step S1 is ultrasonically dispersed in deionized water at a solid-liquid ratio of 1 g:30 mL, and tris(hydroxymethyl)aminomethane is added, and the pH is maintained at 8 to obtain a mixed solution, wherein the mass ratio of tris(hydroxymethyl)aminomethane to the composite filler is 8:1, and then dopamine is added to the mixed solution, stirred at room temperature for 13 hours, and reacted to obtain a suspension, wherein the mass ratio of dopamine to the composite filler is 2:1, and finally, the suspension is placed in a high-speed centrifuge, centrifuged at a rate of 8000 r / min for 30 minutes, and the precipitate is collected, and then the precipitate is washed and dried to obtain a polydopamine-coated filler;

[0055] S3: Add 4,4′-dicyclohexylmethane diisocyanate to prepare component A

[0056] Heat polytetrahydrofuran ether diol at 95° C. and stir for 20 min under nitrogen protection, add 4,4′-dicyclohexylmethane diisocyanate when the temperature of polytetrahydrofuran ether diol drops to 30° C., and then heat and stir at 70° C. for 2 h to react, filter, and obtain a precursor product, wherein the molar ratio of polytetrahydrofuran ether diol to 4,4′-dicyclohexylmethane diisocyanate is 1.5:1, then add the polydopamine coated filler obtained in step S2 to the precursor product at a solid-liquid ratio of 1 g:55 mL, stir and mix evenly, and obtain component A;

[0057] S4: Preparation of fluorinated maleates

[0058] Maleic anhydride and ethylene glycol monododecafluoroheptyl ether are added to a reactor at a molar ratio of 1:2, stirred and mixed to obtain a mixed reaction liquid, and then aminosulfonic acid and toluene are added to the mixed reaction liquid, stirred and mixed to obtain a mixed reaction liquid, and then heated at 110° C. for 14 hours to react to obtain a crude product, wherein the amount of aminosulfonic acid added is 0.6 g / 0.1 mol of maleic anhydride, and the mass ratio of toluene to aminosulfonic acid is 6.5:1. Finally, the crude product is filtered to remove aminosulfonic acid, and then reduced pressure distillation is performed to remove impurities to obtain fluorine-containing maleate;

[0059] S5: Add fluorinated maleate to prepare component B

[0060] The amino-terminated polyether and the epoxy-terminated silicone oil were stirred and mixed uniformly at a molar ratio of 1.5:1, and then heated at 80°C for 8 hours under the protection of nitrogen to react to obtain an intermediate. When the intermediate was cooled to 50°C, the fluorinated maleate prepared in step S4 was added, and then the temperature was raised to 75°C, and the mixture was reacted for 4 hours while stirring to obtain component B, wherein the molar ratio of the fluorinated maleate to the amino-terminated polyether was 1.8:1;

[0061] S6: Mixing component A and component B to prepare polyurea coating

[0062] When in use, the above component A and component B are uniformly mixed in a mass ratio of 1:1 to obtain a polyurea coating.

[0063] Example 2

[0064] A method for preparing a two-component transparent polyurea coating comprises the following steps:

[0065] S1: Preparation of composite fillers by adding antimony tin oxide and nano-silicon dioxide

[0066] Antimony tin oxide and nano-silicon dioxide were added to deionized water at a mass ratio of 2.5:1 according to a solid-liquid ratio of 1g:50mL, ultrasonically dispersed for 25min, and then p-aniline sulfonic acid was added. After stirring and dispersion, the mixture was heated at 75°C for 9h to react to obtain a suspension, wherein the mass ratio of the total amount of antimony tin oxide and nano-silicon dioxide to p-aniline sulfonic acid was 1:16.5. The suspension was then filtered with an aqueous microporous mixed cellulose lipid membrane, washed twice with deionized water and ethanol respectively, and freeze-dried to obtain a surface functionalized mixed material. Subsequently, the mixture was subjected to a solid-liquid ratio of 1g:50mL. 1g: 25mL The surface functionalized mixed material is added into deionized water, ultrasonically dispersed for 15min, and then aniline is added, and stirred at a temperature of 6°C for 35min, uniformly mixed to obtain a dispersion, wherein the mass ratio of aniline to the surface functionalized material is 19:1, finally, phytic acid is added to the dispersion while keeping the temperature constant until the phytic acid concentration reaches 1mol / L, and then ammonium persulfate is added, stirred for reaction for 11h, filtered, washed and freeze-dried to obtain a composite filler, wherein the mass ratio of ammonium persulfate to the surface functionalized material is 22:1;

[0067] S2: Preparation of polydopamine-coated fillers by adding dopamine

[0068] The composite filler prepared in step S1 is ultrasonically dispersed in deionized water at a solid-liquid ratio of 1 g:35 mL, and tris(hydroxymethyl)aminomethane is added, and the pH is maintained at 8.5 to obtain a mixed solution, wherein the mass ratio of tris(hydroxymethyl)aminomethane to the composite filler is 10:1, and then dopamine is added to the mixed solution, stirred at room temperature for 14 hours, and reacted to obtain a suspension, wherein the mass ratio of dopamine to the composite filler is 3:1, and finally, the suspension is placed in a high-speed centrifuge, centrifuged at a rate of 9000 r / min for 35 minutes, and the precipitate is collected, and then the precipitate is washed and dried to obtain a polydopamine-coated filler;

[0069] S3: Add 4,4′-dicyclohexylmethane diisocyanate to prepare component A

[0070] The polytetrahydrofuran ether diol was heated and stirred at 98°C for 25 minutes under nitrogen protection, and when the polytetrahydrofuran ether diol was cooled to 35°C, 4,4′-dicyclohexylmethane diisocyanate was added, and then heated and stirred at 75°C for 3 hours to react, and filtered to obtain a precursor product, wherein the molar ratio of the polytetrahydrofuran ether diol to the 4,4′-dicyclohexylmethane diisocyanate was 2:1, and then the polydopamine-coated filler obtained in step S2 was added to the precursor product at a solid-liquid ratio of 1g:65mL, and stirred and mixed evenly to obtain component A;

[0071] S4: Preparation of fluorinated maleates

[0072] Maleic anhydride and ethylene glycol monododecafluoroheptyl ether are added to a reactor at a molar ratio of 1:2.5, stirred and mixed to obtain a mixed reaction liquid, and then aminosulfonic acid and toluene are added to the mixed reaction liquid, stirred and mixed to obtain a mixed reaction liquid, and then heated at 115° C. for 16 hours to react to obtain a crude product, wherein the amount of aminosulfonic acid added is 0.7 g / 0.1 mol of maleic anhydride, and the mass ratio of toluene to aminosulfonic acid is 7.5:1. Finally, the crude product is filtered to remove aminosulfonic acid, and then reduced pressure distillation is performed to remove impurities to obtain fluorine-containing maleate;

[0073] S5: Add fluorinated maleate to prepare component B

[0074] The amino-terminated polyether and the epoxy-terminated silicone oil were stirred and mixed uniformly at a molar ratio of 2:1, and then heated at 85°C for 9 hours under the protection of nitrogen to react to obtain an intermediate. When the intermediate was cooled to 55°C, the fluorinated maleate obtained in step S4 was added, and then the temperature was raised to 80°C, and the mixture was reacted with stirring for 4.5 hours to obtain component B, wherein the molar ratio of the fluorinated maleate to the amino-terminated polyether was 1.9:1;

[0075] S6: Mixing component A and component B to prepare polyurea coating

[0076] When in use, the above component A and component B are uniformly mixed in a mass ratio of 1:2 to obtain a polyurea coating.

[0077] Example 3

[0078] A method for preparing a two-component transparent polyurea coating comprises the following steps:

[0079] S1: Preparation of composite fillers by adding antimony tin oxide and nano-silicon dioxide

[0080] Antimony tin oxide and nano-silicon dioxide were added to deionized water at a mass ratio of 3:1 according to a solid-liquid ratio of 1g:55mL, ultrasonically dispersed for 30min, and then p-aniline sulfonic acid was added. After stirring and dispersion, the mixture was heated at 80°C for 10h to react to obtain a suspension, wherein the mass ratio of the total amount of antimony tin oxide and nano-silicon dioxide to p-aniline sulfonic acid was 1:18. The suspension was then filtered using an aqueous microporous mixed cellulose lipid membrane, washed with deionized water and ethanol for 3 times respectively, and freeze-dried to obtain a surface functionalized mixed material. Subsequently, the mixture was prepared by mixing the mixture at a solid-liquid ratio of 1g. : 30mL of the surface functionalized mixed material was added into deionized water, ultrasonically dispersed for 20 minutes, and then aniline was added, and stirred at a temperature of 10°C for 40 minutes to uniformly mix to obtain a dispersion, wherein the mass ratio of aniline to the surface functionalized material was 20:1. Finally, phytic acid was added to the dispersion while keeping the temperature constant until the phytic acid concentration reached 1 mol / L, and then ammonium persulfate was added, stirred for reaction for 12 hours, filtered, washed and freeze-dried to obtain a composite filler, wherein the mass ratio of ammonium persulfate to the surface functionalized material was 24:1.

[0081] S2: Preparation of polydopamine-coated fillers by adding dopamine

[0082] The composite filler prepared in step S1 is ultrasonically dispersed in deionized water at a solid-liquid ratio of 1 g:40 mL, and tris(hydroxymethyl)aminomethane is added, and the pH is maintained at 9 to obtain a mixed solution, wherein the mass ratio of tris(hydroxymethyl)aminomethane to the composite filler is 12:1, and then dopamine is added to the mixed solution, stirred at room temperature for 15 hours, and reacted to obtain a suspension, wherein the mass ratio of dopamine to the composite filler is 4:1, and finally, the suspension is placed in a high-speed centrifuge, centrifuged at a rate of 10000 r / min for 40 minutes, and the precipitate is collected, and then the precipitate is washed and dried to obtain a polydopamine-coated filler;

[0083] S3: Add 4,4′-dicyclohexylmethane diisocyanate to prepare component A

[0084] Heat polytetrahydrofuran ether diol at 100° C. and stir for 30 min under nitrogen protection, add 4,4′-dicyclohexylmethane diisocyanate when the temperature of polytetrahydrofuran ether diol drops to 40° C., and then heat and stir at 80° C. for 4 h to react, filter, and obtain a precursor product, wherein the molar ratio of polytetrahydrofuran ether diol to 4,4′-dicyclohexylmethane diisocyanate is 2.5:1, then add the polydopamine coated filler obtained in step S2 to the precursor product at a solid-liquid ratio of 1 g:75 mL, stir and mix evenly, and obtain component A;

[0085] S4: Preparation of fluorinated maleates

[0086] Maleic anhydride and ethylene glycol monododecafluoroheptyl ether are added to a reactor at a molar ratio of 1:3, stirred and mixed to obtain a mixed reaction liquid, and then aminosulfonic acid and toluene are added to the mixed reaction liquid, stirred and mixed to obtain a mixed reaction liquid, and then heated at 120° C. for 18 hours to react to obtain a crude product, wherein the amount of aminosulfonic acid added is 0.8 g / 0.1 mol of maleic anhydride, and the mass ratio of toluene to aminosulfonic acid is 8.5:1. Finally, the crude product is filtered to remove aminosulfonic acid, and then reduced pressure distillation is performed to remove impurities to obtain fluorine-containing maleate;

[0087] S5: Add fluorinated maleate to prepare component B

[0088] The amino-terminated polyether and the epoxy-terminated silicone oil were stirred and mixed uniformly at a molar ratio of 2.5:1, and then heated at 90°C for 10 hours under the protection of nitrogen to react to obtain an intermediate. When the intermediate was cooled to 60°C, the fluorinated maleate prepared in step S4 was added, and then the temperature was raised to 85°C, and the mixture was reacted for 5 hours while stirring to obtain component B, wherein the molar ratio of the fluorinated maleate to the amino-terminated polyether was 2.2:1;

[0089] S6: Mixing component A and component B to prepare polyurea coating

[0090] When in use, the above component A and component B are uniformly mixed in a mass ratio of 1:3 to obtain a polyurea coating.

[0091] Then, the polyurea coating prepared in Examples 1-3 was sprayed on the surface of the copper plate. After drying and curing, the performance of the formed polyurea coating was tested. The test results are shown in Table 1 below:

[0092] 1. Using a thermogravimetric analyzer, the high temperature resistance performance of the polyurea coatings formed by the polyurea coatings in Examples 1-3 was tested respectively;

[0093] 2. According to GB / T23987-2009 standard, the polyurea coatings formed by the polyurea coatings in Examples 1-3 were subjected to an artificial aging test using ultraviolet light;

[0094] 3. According to GB / T1733-1993, the water resistance of the polyurea coatings formed by the polyurea coatings in Examples 1-3 was tested respectively;

[0095] 4. According to GB / T1731-2020, the flexibility of the polyurea coatings formed by the polyurea coatings in Examples 1-3 was tested respectively.

[0096] Table 1: Summary of performance test results of Examples 1-3

[0097]

[0098] Comparative Example 1

[0099] The difference between this comparative example and Example 1 is that steps S1 and S2 are removed, and the polydopamine coated filler in step S3 is removed, and then the performance test is carried out according to the performance test method in Example 1, and the results are shown in Table 2 below.

[0100] Table 2: Comparative Example 1 and Example 1 Performance Test Results Comparison Table

[0101]

[0102] As shown in Table 2 above, in Comparative Example 1, after no polydopamine-coated filler is added, the mass loss temperature of the obtained polyurea coating is about 195°C, and cracks and slight deformation are found after artificial weathering, that is, its high temperature resistance and aging resistance are worse than those of Example 1. It can be seen that by mixing and dispersing antimony tin oxide and nano-silicon dioxide in deionized water, reacting with p-anilinesulfonic acid to perform surface functionalization, and then reacting with aniline and phytic acid under the initiation of ammonium persulfate to form a composite filler, and finally coating the composite filler with polydopamine to improve the compatibility between the composite filler and the polyurea coating, and adding the polydopamine-coated filler to the polyurea coating, the thermal stability and aging resistance of the polyurea coating can be effectively improved, thereby extending the service life of the polyurea coating.

[0103] Comparative Example 2

[0104] The difference between this comparative example and Example 1 is that step S4 is removed, and the fluorinated maleate in step S5 is replaced by an equal amount of maleate not containing fluorine element, and then the performance test is carried out according to the performance test method in Example 1, and the results are shown in Table 3 below.

[0105] Table 3: Comparative Example 2 and Example 1 Performance Test Results Comparison Table

[0106]

[0107] As shown in Table 3 above, the mass loss temperature in Comparative Example 2 was about 205°C, and slight peeling and blistering occurred after the water resistance test. It can be seen that by first reacting maleic anhydride and ethylene glycol monododecafluoroheptyl ether under the catalysis of aminosulfonic acid to prepare fluorinated maleate, then reacting the fluorinated maleate with the intermediate to prepare component A, and mixing component A with component B to prepare a polyurea coating, due to the introduction of fluorinated groups, fluorine atoms have a good protective effect on the molecular chain, thereby effectively improving the water resistance and high temperature resistance of the polyurea coating.

[0108] Comparative Example 3

[0109] The difference between this comparative example and Example 1 is that terminal epoxy silicone oil and terminal amino polyether are not used for reaction, that is, the intermediate in step S5 is replaced by an equal amount of terminal epoxy silicone oil, and then the performance test is carried out according to the performance test method in Example 1, and the results are shown in Table 4 below.

[0110] Table 4: Comparative Example 3 and Example 1 Performance Test Results Comparison Table

[0111]

[0112] As shown in Table 4 above, the mass loss temperature in Comparative Example 3 is about 210°C, and the flexibility is greater than 3mm. It can be seen that by heating the amino-terminated polyether and the epoxy-terminated silicone oil to react to form an intermediate, and then mixing the intermediate with a fluorinated maleate to react to form component A, and mixing component A with component B to form a polyurea coating, the epoxy-terminated silicone oil migrates to the molecular surface, thereby increasing the decomposition temperature, thereby effectively improving the high temperature resistance of the polyurea coating. Moreover, since the epoxy-terminated silicone oil segment is elastic and flexible, and the polyurea segment is rigid, the flexible and rigid segments are combined with each other, and can be better curled and deformed, thereby improving the toughness of the polyurea coating.

[0113] Comparative Example 4

[0114] The difference between this comparative example and Example 1 is that step S2 is removed, and the polydopamine coated filler in step S3 is replaced with an equal amount of composite filler, and then a performance test is performed according to the performance test method in Example 1, and the results are shown in Table 5 below.

[0115] Comparative Example 5

[0116] The difference between this comparative example and Example 1 is that step 1 and step S2 are removed, and the polydopamine-coated filler in step S3 is replaced by equal amounts of antimony tin oxide and nano-silicon dioxide, wherein the mass ratio of antimony tin oxide to nano-silicon dioxide is 2:1. Then, a performance test is carried out according to the performance test method in Example 1, and the results are shown in Table 5 below.

[0117] Table 5: Comparative Example 4-5 and Example 1 Performance Test Results Comparison Table

[0118]

[0119] As shown in Table 5 above, the mass loss temperature in Comparative Example 4 is about 240°C, which is lower than that in Example 1, and there is no crack but slight deformation after artificial weathering aging. The mass loss temperature in Comparative Example 5 is about 225°C, which is lower than that in Example 1, and slight cracks and slight deformation appear after artificial weathering aging. This indicates that by mixing antimony tin oxide and nano-silicon dioxide and dispersing them in deionized water, reacting them with p-anilinesulfonic acid to perform surface functionalization, and then reacting them with aniline and phytic acid under the initiation of ammonium persulfate to form a composite filler, and finally coating the composite filler with polydopamine, the compatibility between the composite filler and the polyurea coating can be improved, thereby improving the thermal stability and aging resistance of the obtained polyurea coating.

[0120] Comparative Example 6

[0121] The difference between this comparative example and Example 1 is that the antimony tin oxide in step S1 is replaced by an equal amount of nano-silicon dioxide, and then a performance test is performed according to the performance test method in Example 1, and the results are shown in Table 6 below.

[0122] Comparative Example 7

[0123] The difference between this comparative example and Example 1 is that the nano-silicon dioxide in step S1 is replaced by an equal amount of antimony tin oxide, and then a performance test is performed according to the performance test method in Example 1, and the results are shown in Table 6 below.

[0124] Table 6: Comparative Example 6-7 and Example 1 Performance Test Results Comparison Table

[0125]

[0126] As shown in Table 6 above, the mass loss temperatures in Comparative Examples 6 and 7 are 245°C and 250°C, respectively, both lower than that in Example 1, and there are no cracks but slight deformation after artificial weathering aging. It can be seen that the simultaneous addition of antimony tin oxide and nano-silicon dioxide can synergistically improve the thermal stability and aging resistance of the obtained polyurea.

[0127] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a two-component transparent polyurea coating, characterized in that: The steps include: S1: Preparation of composite fillers by adding antimony tin oxide and nano-silicon dioxide Antimony tin oxide and nano silicon dioxide are dispersed in deionized water, p-aniline sulfonic acid is added to react, and then mixed with aniline, phytic acid and ammonium persulfate to react to obtain a composite filler; S2: Preparation of polydopamine-coated fillers by adding dopamine The composite filler is dispersed in deionized water, and then tris(hydroxymethyl)aminomethane and dopamine are added to react to obtain a polydopamine-coated filler; S3: Add 4,4′-dicyclohexylmethane diisocyanate to prepare component A Heat and stir polytetramethylene glycol, then add 4,4′-dicyclohexylmethane diisocyanate to react, and then add the polydopamine coated filler to obtain component A; S4: Preparation of fluorinated maleates Maleic anhydride and ethylene glycol monododecafluoroheptyl ether are stirred and mixed, and aminosulfonic acid and toluene are added to react to obtain fluorine-containing maleate; S5: Add fluorinated maleate to prepare component B The amino-terminated polyether and the epoxy-terminated silicone oil are stirred and mixed to react, and then the fluorinated maleate is added to react to obtain component B; S6: Mixing component A and component B to prepare polyurea coating When in use, the above component A and component B are uniformly mixed in a mass ratio of 1:(1-3) to obtain a polyurea coating.

2. The method for preparing a two-component transparent polyurea coating according to claim 1, characterized in that: S1 specifically includes the following steps: S1.1: Add antimony tin oxide and nano-silicon dioxide in a mass ratio of (2-3):1 into deionized water at a solid-liquid ratio of 1g:(45-55)mL, and disperse them by ultrasonic for 20-30min. Then add p-anilinesulfonic acid, stir and disperse, and heat at 70-80℃ for 8-10h to react to obtain a suspension. S1.2: filtering the suspension through a water-based microporous mixed cellulose lipid membrane, washing with deionized water and ethanol for 2-3 times respectively, and freeze-drying to obtain a surface functionalized mixed material; S1.3: Add the surface functionalized mixture to deionized water at a solid-liquid ratio of 1 g: (20-30) mL, disperse by ultrasonic for 10-20 min, then add aniline, stir at 2-10°C for 30-40 min, and mix evenly to obtain a dispersion; S1.4: Keeping the temperature constant, add phytic acid to the above dispersion until the phytic acid concentration reaches 1 mol / L, then add ammonium persulfate, stir and react for 10-12 hours, filter, wash and freeze-dry to obtain a composite filler.

3. The method for preparing a two-component transparent polyurea coating according to claim 2, characterized in that: S2 specifically includes the following steps: S2.1: ultrasonically disperse the composite filler obtained in step S1.4 in deionized water at a solid-liquid ratio of 1 g: (30-40) mL, then add tris(hydroxymethyl)aminomethane, maintain the pH at 8-9, and obtain a mixed solution; S2.2: Add dopamine to the mixed solution, stir at room temperature for 13-15 hours to react and obtain a suspension; S2.3: Place the above suspension in a high-speed centrifuge, centrifuge at a rate of 8000-10000 r / min for 30-40 min, collect the precipitate, and then wash and dry the precipitate to obtain a polydopamine-coated filler.

4. The method for preparing a two-component transparent polyurea coating according to claim 3, characterized in that: S3 specifically includes the following steps: S3.1: Heat polytetrahydrofuran ether diol at 95-100°C with stirring for 20-30 min under nitrogen protection; S3.2: When the temperature of polytetramethylene glycol is reduced to 30-40°C, 4,4′-dicyclohexylmethane diisocyanate is added, and then heated at 70-80°C while stirring for 2-4 hours to react, and filtered to obtain a precursor product, wherein the molar ratio of polytetramethylene glycol to 4,4′-dicyclohexylmethane diisocyanate is (1.5-2.5):1; S3.3: Add the polydopamine-coated filler obtained in step S2.3 to the above-mentioned precursor product at a solid-liquid ratio of 1g:(55-75)mL, stir and mix evenly to obtain component A.

5. The method for preparing a two-component transparent polyurea coating according to claim 3, characterized in that: S4 specifically includes the following steps: S4.1: maleic anhydride and ethylene glycol monododecafluoroheptyl ether are added into a reactor at a molar ratio of 1:(2-3), and stirred to mix well to obtain a mixed reaction liquid; S4.2: Add sulfamic acid and toluene to the mixed reaction solution, stir and mix evenly, and then heat at 110-120° C. for 14-18 hours to react to obtain a crude product; S4.3: The crude product is filtered to remove aminosulfonic acid, and then distilled under reduced pressure to remove impurities to obtain fluorinated maleate.

6. The method for preparing a two-component transparent polyurea coating according to claim 3, characterized in that: S5 specifically includes the following steps: S5.1: Mix the amino-terminated polyether and the epoxy-terminated silicone oil in a molar ratio of (1.5-2.5): 1 and then heat at 80-90°C for 8-10h under the protection of nitrogen to react and obtain an intermediate; S5.2: When the intermediate is cooled to 50-60°C, the fluorinated maleate prepared in step S4.3 is added, and then the temperature is raised to 75-85°C, and the mixture is reacted for 4-5 hours while stirring to obtain component B, wherein the molar ratio of the fluorinated maleate to the amino-terminated polyether is (1.8-2.2):

1.

7. The method for preparing a two-component transparent polyurea coating according to claim 3, characterized in that: The mass ratio of the total amount of antimony tin oxide and nano-silicon dioxide to p-aniline sulfonic acid is 1:(15-18), the mass ratio of aniline to the surface functional material is (18-20):1, and the mass ratio of ammonium persulfate to the surface functional material is (20-24):

1.

8. The method for preparing a two-component transparent polyurea coating according to claim 1, characterized in that: The mass ratio of tris(hydroxymethyl)aminomethane to the composite filler is (8-12):1, and the mass ratio of dopamine to the composite filler is (2-4):

1.

9. The method for preparing a two-component transparent polyurea coating according to claim 4, characterized in that: The amount of aminosulfonic acid added is (0.6-0.8) g / 0.1 mol maleic anhydride, and the mass ratio of toluene to aminosulfonic acid is (6.5-8.5):

1.

10. A two-component transparent polyurea coating, characterized in that: The two-component transparent polyurea coating is prepared by the method for preparing the two-component transparent polyurea coating according to any one of claims 1 to 9.

Citation Information

Cited By

  • Preparation method and application of high-transparency corrosion-resistant polyaspartic polyurea coating and coating

    CN122706231A